Combined administration of low molecular weight sodium alginate boosted immunomodulatory, disease resistance and growth enhancing effects of Lactobacillus plantarum in Nile tilapia (Oreochromis niloticus) - Van Doan H. (2017)
© 2016 Elsevier Ltd The present study investigates the effects of combined or singular administration of low molecular weight sodium alginate (LWMSA) and Lactobacillus plantarum on innate immune response, disease resistance and growth performance of Nile tilapia (Oreochromis niloticus). Three hundred and twenty fish were supplied and randomly stocked in sixteen glass tanks (150 L) assigned to four treatments as follows: 0 g kg −1 LMWSA (Control, Diet 1), 10 g kg −1 LMWSA (Diet 2), 10 8 CFU g −1 L. plantarum (Diet 3), and 10 g kg −1 LMWSA + 10 8 CFU g −1 L. plantarum (Diet 4). Following 30 and 60 days of the feeding trial, serum lysozyme, phagocytosis, respiratory burst and alternative complement activities as well as growth performance parameters (specific growth rate, feed conversion ratio) were measured. Serum lysozyme, phagocytosis, respiratory burst, and alternative complement activities of fish were significantly stimulated by both LMWSA and L. plantarum diets, however, the highest innate immune response were observed in fish fed synbiotic diet. At the end of the experiment, eight fish per replication were randomly selected for a challenge test against Streptococcus agalactiae. The survival rate of the fish fed supplemented diets was significantly greater than the control treatment and the highest post challenge survival rate was observed in synbiotic diet. Furthermore, SGR and FCR were significantly improved in fish fed supplemented diets after 60 days and the highest growth performance was observed in fish fed synbiotic diet. These results suggest combined LMWSA and L. plantarum can be considered as a promising immunostimulant and growth enhancer in Nile tilapia diet.